New coronavirus infection in pediatric practice: clinical and epidemiological features of COVID-19 in the city of Smolensk - V. V. Sokolovskaya; A. A. Litvinova; D. A. Balukhto; I. N. Kuzmina; A. V. Krikova; R. S. Kozlov (Детские инфекции (Москва))
The aim of the study was to study the clinical and epidemiological features of the new COVID-19 coronavirus infection in children hospitalized in the infectious department. Material and methods. 249 case histories of patients from 0 to 18 years of age who are on inpatient treatment at «Clinical Hospital N1» in Smolensk for the period from April 2020 to July 2022 were studied by the continuous sampling method. Verification of a new coronavirus infection was carried out by examining smears from the nasopharynx and oropharynx for the presence of SARS-CoV-2 by real-time PCR. Results. The prevalence of patients from 1 to 3 (19.3%, 49.1%) and from 6—15 (15.8%, 50.5%) years was revealed both in 2020 and in 2021 and the first half of 2022. No significant differences in gender were found. The largest number of cases in 2020 was registered in April (16%) and November (14%), in 2021 — in December (18%) and November (16%). The prevailing severity in both 2020 and 2021, 2022 was the average severity (63% , 72%, 93%, respectively). The main syndromes of COVID-19 have been identified: intoxication syndrome, respiratory catarrhal syndrome, bronchopulmonary, intestinal. Bilateral pneumonia was most often detected (47% in 2020 , 44% in 2021, 62% in 2022), right-sided pneumonia (33% in 2020, 30% in 2021, 31% in 2022 ), and left-sided pneumonia (20%, 26% and 7%, respectively). The main comorbid pathologies are noted, and cases of somatic diseases first registered against the background of COVID-19 are described.